Do the two components have a common origin in coexisting tumor of craniopharyngioma and pituitary adenoma?. (January 2023) - Sun, Sishuai; Yang, Chen; Feng, Fan; Zhong, Hanlin; Ma, Shengting; Huang, Bin; Ni, Shilei; Li, Xingang
Abstract: The coexistence of craniopharyngioma and pituitary adenoma in sellar region increased gradually in recent years. The origin for the two types of tumor cells has become controversial. We have reviewed the recent literatures and proposed a hypothesis: The origin of tumor cells is related to the type of craniopharyngioma in the coexisting tumors of craniopharyngioma and pituitary adenoma. The two tumor cells originate from different precursor cells if craniopharyngioma is papillary craniopharyngioma and the same kind of precursor cell if craniopharyngioma is adamantinomatous craniopharyngioma, which is derived from the proliferation of pituitary progenitor/stem cells induced by the accumulation of oncogenic β-catenin. This hypothesis is helpful to complete the coexisting process of craniopharyngioma and pituitary adenoma. Meanwhile, it is of great significance to reveal the causes of coexisting tumor in sellar region.